The Legal Protection of Personal Data in the Perspective of Human Rights - Suwondo, Denny (Universitas Islam Sultan Agung, 2023)
In the history of its development, privacy is a concept that is universal and recognized in various countries both written in the form of laws and unwritten in the form of moral rules. Protection of personal rights or private rights will increase human values, improve the relationship between individuals and their communities, increase independence or autonomy to exercise control and obtain decency, and increase tolerance and keep away from discrimination and limit government power. The purpose of this research is to discuss the Construction of Personal Data Protection Arrangement in Indonesia and Personal Data Protection from Human Rights Perspective. Law No. 27 of 2022 on Personal Data Protection, it can be observed that there is some progressiveness regarding personal data in Indonesia. It can be seen in terms of legal politics, understanding, information, personal data processors, personal data controllers, and personal data subjects who are not only people but also companies / legal entities. So that the politics of law in this arrangement can be seen in the active role of the government starting from regulation, storage, processing, transfer, to countermeasures both preventively and repressively (imposition of sanctions). Novelty in this research is that regulatory efforts related to the right to privacy of personal data are a manifestation of the recognition and protection of basic human rights. Therefore, the preparation of the Law on Personal Data Protection has a strong philosophical foundation and can be accounted.